Do heart failure inpatients present a suitable selfmanagement of their disease? - Delgado, Bruno (2020)
Heart failure (HF) is a syndrome that conduct patients to high levels of impairment. Knowing the symptoms of the disease and being aware about the most important aspects related to a good selfmanagement is very important. The first step to improve knowledge is to know what patients really understand about HF and what are they capable of doing, in order to control the disease. Purpose To characterize the level of selfmanagement of the disease on patients admitted due to decompensated HF Methods Using the Self Care Heart Failure Index (SCHFI), 92 inpatients were evaluated in order to understand their level of awareness about selfcare in HF and what are the main strategies used when they identify symptoms of decompensation. Variables like age, gender and functional status (Barthel index (BI) and LCADL) at admission were used to made some correlations. Descriptive statistics was used to identify the most common strategies used by patients and to analyze the selfcare items of the scale. Results The mean age was 70 (±9,4) years and patients were mainly male (66,7%). They presented high levels of functional impairment with 32 points on LCADL and 73 on BI and a mean of 4 cardiovascular risk factors. Regarding section A, the three most frequent instructions performed by patients was: 1) Avoid getting sick, 2) keep doctor or nurse appointments and 3) Don´t forget to take the medicines. The most notfollowed instructions were: 1) Do some physical activity or Exercise for 30 minutes, 2) Weight themselves and 3) check ankles for swelling. Regarding section B only 7,6% of the patients immediately recognized the symptom of HF decompensation and 57,6% did not. 64,1% of the patients refers Very likely to Call the doctor or nurse for attendance. Section C refers to confidence of patients in selfmanagement, 53% of the patients refer to be not confident about any of the items of the list. The mean score of the scale was 43 (±10) points. Regarding correlations, patients who refer to perform same physical activity or exercise at least 30 minutes show a negative correlation with number of CVRF and LCADL at admission and a positive correlation with BI at admission. Conclusions Patients demonstrate high confidence on their health team providers, however they do not perform correctly the instructions given and showed difficulties in identifying symptoms of decompensation. Self management and knowledge must be improved to these patients. Other study must be devolved in order to understand the causes for this results. Conclusions Patients demonstrate high confidence on their health team providers, however they do not perform correctly the instructions given and showed difficulties in identifying symptoms of decompensation. Self management and knowledge must be improved to these patients. Other study must be devolved in order to understand the causes for this results.